The impact of augmented reality on cognitive load and performance: A systematic review - Buchner, Josef; Buntins, Katja; Kerres, Michael (Journal of computer assisted learning, 2022)
Background Previous studies on augmented reality‐enriched learning and training indicated conflicting results regarding the cognitive load involved: some authors report that AR can reduce cognitive load, others have shown that AR is perceived as cognitively demanding and can lead to poorer performance. Objectives The aim of this study is to systematically analyse previous research on AR and cognitive load, including performance, and thus to be able to contribute to answering the question of the impact of AR on cognitive load when used in learning environments. Methods This study applied the systematic review method. A total of 58 studies were identified and analysed using rigorously defined inclusion and exclusion criteria. The results are now reported as a synthesis. Results and Conclusions Compared to other technologies, AR seems to be less cognitively demanding and also leads to higher performance. However, these results are based on media comparison studies that have been criticized for years. The spatial AR type is better compared to see‐through AR. However, the latter can be improved by visual cues and the addition of learning activities, such as value‐added studies have revealed. Major takeaways The essential findings of this study are that the technology used, for example, AR glasses, can unnecessarily increase cognitive load and that still many studies focus on the comparison of AR with more traditional media. Less studies applied alternative research designs, for example, value‐added comparisons. However, such designs are better suited to investigate design principles for AR‐enriched learning environments, which can then in turn reduce cognitive load as well as positively affect performance. Lay Description What is already known about this topic Augmented reality can be an effective technology for learning and training purposes. However, findings with regard to cognitive load levels in AR‐enriched learning environments are contradictory. What this paper adds AR can be superior with regard to cognitive load and performance compared to other media. Spatial AR is perceived less cognitively demanding compared to see‐through AR. The effect of AR‐enriched learning and training on cognitive load and performance is more clearly for procedural knowledge acquisition. Research on AR and cognitive load is merely based on media comparison studies, while value‐added studies might better contribute to the question how to use AR for teaching and learning. Implications for practice and/or policy AR is well suited to assist and support procedural knowledge acquisition and tasks. Currently, spatial AR should be preferred over see‐through AR, since see‐through AR still leads to a high cognitive load. If see‐through AR is still used, visual cues and learning activities should be employed as a supplement, as these can reduce cognitive load and thus contribute to better performance.